2013
DOI: 10.1214/13-aos1127
|View full text |Cite
|
Sign up to set email alerts
|

Optimal detection of sparse principal components in high dimension

Abstract: We perform a finite sample analysis of the detection levels for sparse principal components of a high-dimensional covariance matrix. Our minimax optimal test is based on a sparse eigenvalue statistic. Alas, computing this test is known to be NP-complete in general, and we describe a computationally efficient alternative test using convex relaxations. Our relaxation is also proved to detect sparse principal components at near optimal detection levels, and it performs well on simulated datasets. Moreover, using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
256
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(264 citation statements)
references
References 75 publications
8
256
0
Order By: Relevance
“…In passing, we note that there is a very interesting line of work on exact or approximate support reconstruction for sparse PCA, i.e., estimating correctly or consistently the positions of non-zeros in v, in a regime where the size of the support is sublinear in n (see e.g., [28,5,12,32,21] and references therein) 1 . In an influential paper [28], it was shown that while the estimate via the classical PCA is inconsistent, a simple diagonal thresholding procedure consistently estimates v provided that v is sufficiently sparse.…”
Section: Sparse Pcamentioning
confidence: 99%
“…In passing, we note that there is a very interesting line of work on exact or approximate support reconstruction for sparse PCA, i.e., estimating correctly or consistently the positions of non-zeros in v, in a regime where the size of the support is sublinear in n (see e.g., [28,5,12,32,21] and references therein) 1 . In an influential paper [28], it was shown that while the estimate via the classical PCA is inconsistent, a simple diagonal thresholding procedure consistently estimates v provided that v is sufficiently sparse.…”
Section: Sparse Pcamentioning
confidence: 99%
“…Consider the expression for the KL divergence given in (10). Using (3), we obtain KL(P 0 | A || P S | A ) = KL(P 0 || P S∩A )…”
Section: B Proof Of Bound On Kl Divergencementioning
confidence: 99%
“…Besides anomaly detection, detection of correlations is also of interest to assess to what extent dimensionality reduction can be performed on a data stream. Reduction of dimensionality is a workhorse of data analysis, and there has been a strong recent interest in modifying principal component analysis to deal with high-dimensional data [10], [12], [26]. Testing when this type of transformation is justified is thus an important problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2,15] suggested heuristics when the detection levels are unknown, but they are not proven to achieve the optimal detection levels. Berthet et al [47,53] proved whether there exists a polynomial-time computable statistic for reliably detecting the presence of a single spike of 0 l -sparsity. They proved that no polynomial algorithm will reconstruct the support unless kn  .…”
mentioning
confidence: 99%